2019
DOI: 10.1155/2019/7038259
|View full text |Cite
|
Sign up to set email alerts
|

A Travel Route Recommendation System Based on Smart Phones and IoT Environment

Abstract: Tourism recommendation systems play a vital role in providing useful travel information to tourists. However, existing systems rarely aim at recommending tangible itineraries for tourists within a specific POI due to their lack of onsite travel behavioral data and related route mining algorithms. To this end, a novel travel route recommendation system is proposed, which collects tourist onsite travel behavior data automatically regarding a specific POI based on smart phone and IoT technology. Then, the propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…In the study, a clustering scheme was developed to prolong the network lifetime by distributing energy consumption among clusters. In [31], a novel travel route recommendation system was proposed that collected tourist on-site travel behavior data automatically regarding a specific POI that was based on smart phone and Internet of Things technologies. The tour-route-recommendation algorithm was then created to search and rank the tangible travel routes.…”
Section: Addressing Challenges For Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study, a clustering scheme was developed to prolong the network lifetime by distributing energy consumption among clusters. In [31], a novel travel route recommendation system was proposed that collected tourist on-site travel behavior data automatically regarding a specific POI that was based on smart phone and Internet of Things technologies. The tour-route-recommendation algorithm was then created to search and rank the tangible travel routes.…”
Section: Addressing Challenges For Researchmentioning
confidence: 99%
“…Ref. [31] collected tourists' traveling data on the website and analyzed the tourists' behaviour and, based on the website tourists' mobile data as well as the mined POIs, it set up the tour route recommendation algorithm. Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The traffic condition is used to find the best type of vehicle which has waiting time while traveling. Others existing system also tried to combine several attributes to define the routes [41,[52][53][54].…”
Section: Attributes Of Road Situationmentioning
confidence: 99%
“…In [3] the authors identified that current recommendation systems rarely aim at recommending tangible itineraries for tourists within a specific POI due to the lack of onsite travel behavioural data and related route mining algorithms. To this end, a novel travel route recommendation system was proposed, which collected tourist onsite travel behaviour data automatically regarding a specific POI, based on smartphone and Internet of Things (IoT) technology.…”
Section: Introductionmentioning
confidence: 99%